Determination Of Self-Identity Construction Through Integration Of Self-Identity Theory And Adventure Tourism: A Case Study Of Surfing Activities On The South Coast Of Java - Nurdina Prasetyo; Pranoto Pranoto; Sukrisno Sukrisno; Idah Kusuna Dewi (UNIVED Press, 2024)
This research explores the role of self-identity in motivating young Indonesian tourists to participate in adventure tourism, specifically learning to surf on the southern coast of Java. Using a qualitative approach with two-phase interviews, this study involved participants from diverse cultural backgrounds who took surfing lessons at Menganti Beach, Widarapayung, and Parangtritis. Data analysis identified five key constructs influencing attitudes and participation intentions: novelty-seeking, connection to